The Determinants of Financial and Operational Sustainability OF Microfinance Institutions: Case Study of Clecam-Ejoheza Ltd. (Global Journal of Management and Business Research, 2017)
This research is about analysing the determinants of financial and operations sustainability of Microfinance institutions in Rwanda, particularly the case study of CLECAM-EJOHEZA ltd. The study evaluates the financial and operational sustainability of CLECAM-EJOHEZA Ltd through a financial analysis by ratios conducted on the financial statements of CLECAM-EJOHEZA Ltd for the period from 2010 to 2015. For instance, to accomplish the measurement of financial and operational sustainability of a company cited above, financial selfsufficiency ratio (FSS) and operational self-sufficiency ratio (OSS) were used as the dependent variables because the Microfinance Financial Reporting Standards recommends the use of financial self-sufficiency (FSS) and operational self-sufficiency (OSS) as measures of sustainability of the MFI.
Keywords: microfinance; sustainability; financial sustainability; operational sustainability